Tindak Pidana Korupsi Pengadaan Barang Dan Jasa Dalam Hukum Positif Indonesia - Ramadhan, Satria (Prosiding, 2024)
Government procurement of goods/services is an activity to obtain goods/services by Ministries/Agencies/Regional Work Units/other Institutions. Goods/services procurement activities still cause problems resulting in state financial losses. The purpose of writing is to analyze the criminal regulation of corruption in the procurement of goods/services and unlawful acts of misuse of the procurement of goods/services. The formulation of the problem in this paper is: 1) How is the criminal regulation of corruption in the procurement of goods and services regulated in statutory regulations? and 2) What is the unlawful act of abuse of authority in the crime of corruption in the procurement of goods/services? Normative legal research method, the research approach is carried out by reviewing laws and regulations related to the legal issue being researched, using technical literature and document studies. Research data from secondary data sourced from primary legal, secondary legal and tertiary legal materials with qualitative data analysis that describes descriptively. The results of the research show that the crime of corruption in the procurement of goods/services in Indonesian positive law is regulated in Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes, while the accountability of perpetrators of criminal acts of corruption is regulated in Presidential Regulation Number 12 20021 concerning Amendments to Regulation Number 16 of 2018 concerning Procurement of Government Goods/Services. Conclusion: Regulation of Corruption Crimes in Procurement of Goods and Services in Indonesian Positive Law is regulated in Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning Eradication of Corruption Crimes, Presidential Regulation Number 12 of 2021 concerning Amendments to Regulation Number 16 of 2021 2018 concerning Procurement of Government Goods/Services. Position responsibility and personal responsibility in the procurement of goods and services are very important, because these two concepts have implications for criminal responsibility.